Tehranian Elderly People’s Experiences About Leisure Time Activities and Recreations - Abolfazl Rahimi; Monireh Anoosheh; Fazlollah Ahmadi; Mahshid Foroughan (Sālmand, 2010)
Objectives: The aim of this study was to explain the various style of leisure activity and recreation of elderly people in Tehran.